Perfect phrases for ESL conversation skills hundreds of ready-to-use phrases that help you express your thoughts, ideas, and feelings in English conversations of all types - Engelhardt, Diane (New York McGraw Hill, 2022)
This handy reference will help you navigate social and business situations, with hundreds of ready-to-use English phrases and example dialogues for conversing with friends, collaborating with coworkers, and engaging those around you. And the new edition of this bestselling guide includes a new chapter on tele- and video conferencing, as well as audio recordings, available via app, of typical conversations and key phrase clusters throughout the book"--
Part 1 Phrases for conversation. Small talk ; Past experiences ; Likes, dislikes, and interests ; Objects and processes ; Problems and advice ; Decisions and goals -- Part 2 Phrases for discussions. Opinions ; Group discussions ; Serious subjects -- Part 3 Phrases for special occasions. Special occasions -- Part 4 Phrases for telephone and video conversations. Telephone basics ; Telephone messages ; Telephone business ; Telephone/video conferencing.
Audio phrases and conversations via app"--Front cover.
Includes index (231-222)
previous edition: 2017.
Keywords: Adult education; English language -- Terms and phrases; English language -- Textbooks for foreign speakers